Motor impairment and its relationship to fitness in children. Issue 7 (11th July 2013) - Morris, Martyn; Dawes, Helen; Howells, Ken; Janssen, Roel
Abstract : Objectives: The aim of this work was to explore the physiological and perceptual limits to exercise in children with varying degrees of motor impairment, and the relationships to measures of health. Design and methods: In a group comparison design, 35 boys aged 12–15 years completed the Movement ABC test for the assessment of motor impairment, followed by an incremental cycle ergometer test to exhaustion for the assessment of maximal oxygen uptake (VO2peak ), respiratory exchange ratio (RER), heart rate (HR) and rating of perceived exertion (RPE). Ten participants classified as having either high or no motor impairment also performed a maximal voluntary isometric contraction (MVIC) for the assessment of lower limb extensor strength. Results: 18 boys were classified as having high motor impairment. There was a significant difference in peak (34.9 vs 48.5 mL kg/min), workload (12.5 vs 10.0 mL W), maximal HR (176 vs 188 bpm), maximal oxygen pulse (12.1 vs 15.9 mL beat) and MVIC (5.7 vs 9.1 Nm kg) between the high and non-motor impaired participants, respectively, (p<0.05). There was no significant difference in the RER or RPE between groups. Conclusions: When performing cycling ergometry, perceived exertion was not a limiting factor in children with high motor impairment. The lower maximal HR, coupled with reduced movement efficiency and muscle strength reported in this group, suggests that exercise is limited by impairment at the muscular level. This finding was supported by high RER values despite low maximal HR values attained at exercise cessation and reduced maximal strength. Perception of effort is not heightened in children with high motor impairment and future-exercise interventions should be focused on improving muscular condition in these participants to enable them to be better prepared to engage in physical activity for health.